DIGITAL LITERACY, COMPETENCE, AND ORGANIZATIONAL SUPPORT ON MY-ASET SYSTEM EFFECTIVENESS - Anis Sukamto; Bambang Yulianto; Syunu Trihantoyo (STAI Ma'had Aly Al-Hikam Malang, 2026)
Digital transformation in institutional asset management requires robust systems and capable human resources. However, the implementation of the My-Aset Management Information System at Universitas Negeri Surabaya has faces challenges related to technical issues and user adoption in the field. This study aims to analyze the impact of digital literacy, digital competence, and organizational support on the effectiveness of the My-Aset management information system. This quantitative study employed a correlational approach using a questionnaire distributed to a sample of 64 asset management staff. The data were then analyzed using multiple linear regression. The results of the statistical test show that digital literacy (t = 3,530; Sig. = 0,001) and organizational support (t = 6,269; Sig. = 0,000) had a positive and significant impact on the system's effectiveness. Conversely, digital competence showed a significant negative impact (t = -2,332; Sig. = 0,023). Simultaneously, the model is explained 75% of the variaance in the system effectiveness (R² = 0,750). This study conclauded that institutional support and basic literacy can enhance effectiveness; however, high levels of technical competence among employees created a perception of inefficiency when the system’s infrastructure remainded underdeveloped. Consequently, university administrators are advised to prioritize updating the technical features of the My-Aset application to align with the high level of digital proficiency among staff, rather than focusing solely on training. Keywords: Digital literacy; digital competence; organizational support; managemen information system; My-Aset. Abstrak Transformasi digital dalam tata kelola aset institusi menuntut kesiapan sistem dan kapabilitas sumber daya manusia. Namun, implementasi Sistem Informasi Manajemen My-Aset di Universitas Negeri Surabaya dihadapkan pada tantangan kendala teknis dan adaptasi pengguna di lapangan. Penelitian ini bertujuan untuk menganalisis pengaruh literasi digital, kompetensi digital, dan dukungan organisasi terhadap efektivitas sistem informasi manajemen My-Aset. Penelitian kuantitatif ini menggunakan pendekatan korelasional dengan instrumen kuesioner yang didistribusikan kepada sampel sebanyak 64 pegawai pengelola aset. Data kemudian dianalisis menggunakan teknik regresi linier berganda. Hasil uji statistik membuktikan bahwa literasi digital (t = 3,530; Sig. = 0,001) dan dukungan organisasi (t = 6,269; Sig. = 0,000) berpengaruh positif dan signifikan terhadap efektivitas sistem. Sebaliknya, kompetensi digital justru menunjukkan pengaruh negatif yang signifikan (t = -2,332; Sig. = 0,023). Secara simultan, model ini mampu menjelaskan 75% variasi efektivitas sistem (R² = 0,750). Kesimpulan studi ini adalah dukungan institusi dan literasi dasar mampu mendorong efektivitas, namun tingginya kompetensi teknis pegawai justru memunculkan persepsi inefisiensi ketika infrastruktur sistem masih tertinggal. Implikasinya, pimpinan universitas disarankan untuk memprioritaskan pembaruan fitur teknis aplikasi My-Aset agar selaras dengan tingginya keahlian digital pegawai, bukan semata-mata berfokus pada pelatihan. Kata kunci: Literasi digital; kompetensi digital; dukungan organisasi; sistem informasi manajemen; My-Aset.